Epidemiological characteristics and distribution of congenital thumb duplication in south China: An analysis of 2,300 thumbs in 2,108 children - Wu, JianPing; Shi, WeiZhe; Lin, XueMei; Li, JingChun; Yuan, Zhe; Zhu, Mingwei; Liu, YuanZhong; Li, YiQiang; Canavese, Federico; Xu, HongWen (Frontiers in Pediatrics, 2022)
Objective: The objective of this study was to evaluate epidemiological and anatomical characteristics of children with congenital thumb duplication (CTD). Methods: We retrospectively reviewed 2108 children with CTD. Data regarding sex, age at the surgery, laterality, uni- or bilateral involvement, and dominant side were retrieved from the medical charts. Plain radiographs were used to classify all CTD according to Wassel-Flatt, Rotterdam and Chung classification systems and to evaluate the patho-anatomy of the duplication as well as the presence of associated anomaly. Results: A total of 796 girls and 1312 boys with CTD (n=2300 thumbs) met the inclusion criteria. The male to female and unilateral to bilateral ratio were 1.6:1 and 10:1, respectively. Associated anomaly was found in 302/2300 thumbs (13.1%), and the middle phalanx deformity of the 5th finger was the most common one. A dominant thumb, larger and more developed, was on the ulnar side in 2270/2300 cases (98.7%). According to the Wassel-Flatt classification, type IV (40.2%) was the most common deformity and the extra thumb was connected to the main thumb by a joint in most cases (437/780); overall, 15.7% of thumbs (n=360) did not fit the Wassel-Flatt classification. According to the Rotterdam classification, type IV (51.3%) was the most common form; in most cases (363/1180) the thumb was hypoplastic or floating. Overall, 3/2300 thumbs (0.1%) could not be classified according to Rotterdam classification. According to the Chung classification, type A was the most common subtype (44.1%); in most cases (716/1015) the duplication was at the level of the metacarpal bone. Overall, 2/2300 thumbs (0.1%) did not fit the Chung classification. Conclusions: In patients from southern China, CTD shows male and right-sided predominance with ulnar-dominant thumb. Abnormalities of the middle phalanx of the 5th finger are more frequent in patients with associated anomaly. The development of a simple and comprehensive classification system is needed to guide treatment and to adequately assess the epidemiological characteristics of patients with CTD in order to facilitate comparison between different patients’ populations.